Human diseases associated with connexin mutations - Srinivas, Miduturu (Biochim Biophys Acta, 2017)
Gap junctions and hemichannels comprised of connexins impact many cellular processes. Significant advances in our understanding of the functional role of these channels have been made by the identification of a host of genetic diseases caused by connexin mutations. Prominent features of connexin disorders are the inability of other connexins expressed in the same cell type to compensate for the mutated one, and the ability of connexin mutants to dominantly influence the activity of other wild-type connexins. Functional studies have begun to identify some of the underlying mechanisms whereby connexin channel mutation contributes to the disease state. Detailed mechanistic understanding of these functional differences will help to facilitate new pathophysiology driven therapies for the diverse array of connexin genetic disorders.